Perinatal stress moderates the link between early and later emotional skills in very preterm-born children: An 11-year-long longitudinal study. (June 2018) - Dimitrova, Nevena; Turpin, Hélène; Borghini, Ayala; Morisod Harari, Mathilde; Urben, Sébastien; Müller-Nix, Carole
Abstract: Background: Very preterm (VPT) birth refers to an early stressful event putting children at heightened risk for emotional difficulties. However, there is an important individual variability, leaving unexplained why some VPT children do not develop emotional difficulties, while others develop such difficulties in the early years or later in life. Aim: In this study, we examined whether perinatal stress is a risk factor explaining heterogeneities in emotional problems in VPT children. Methods: Thirty-six VPT children and 22 full-term born (FT) children participated in an 11 year-long study. Risk for perinatal stress was assessed at birth with the Perinatal Risk Inventory. Mothers reported children's emotional difficulties at 18 months of child age on the Symptom Checklist and at 11 years on the Child Behavior Checklist. Results: Results indicated significant differences in emotional scores at 11 years not only between VPT and FT children but also between the low and high perinatal stress groups. More importantly, emotional scores at 18 months influenced variability in internalizing scores at 11 years only in VPT children with high perinatal stress. Conclusion: Although prematurity affects the emotional abilities of preadolescents, the link between emotional skills in early and later childhood is moderated by the severity of perinatal stress. In particular, VPT children who are born with more complications, and as such experience a more stressful perinatal environment, are more likely to show emotional difficulties at preadolescence. Highlights: A very premature birth puts children at risk for emotional difficulties. It remains unclear why some children born very preterm (VPT) develop emotional problems while other do not. Perinatal stress might explain individual variability in the development of emotional problems in VPT children. VPT children with higher perinatal stress are more likely to show emotional difficulties later on.